The Suitability Evaluation of Procurement Information Systems to the Needs of Users and Management Using Human, Organization, Technology-Fit (HOT-Fit) Framework - Cahyono, Dwi; Suryani, Erma (IPTEK The Journal for Technology and Science, 2020)
Management Information System (MIS) in government institutions was a crucial thing in supporting good services to the community. The established MIS often provided less optimum benefits since the MIS development did not go through a good planning and was not supported by a clear IT Masterplan so that an evaluation of the MIS implementation is needed, especially from 3 (three) main aspects, including aspects of Human, Organization and Technology. The procurement unit of Malang City has a MIS for procurement submission called siBaja which has been established since 2016. This study aimed to evaluate the suitability of siBaja to the needs of users and management using Human, Organization, Technology-Fit (HOT-Fit) framework with some modifications.To obtain the data, a survey method was used by distributing questionnaires to the application users.The data analysis model used was SEM-PLS by using SmartPLS 3.0 software. This study found that the implementation of siBaja was not fully fit for the relationship between Human-Technology that was indicated by the absence of a significant effect between US variable and SQ variable with a significance value of 0.899 at Î± = 0.05 and was not fully fit for the relationship between Organization-Technology factor which was characterized by the absence of a significant effect between SC variable and IQ variable with a significance value of 0.221 at Î± = 0.05.